Balancing Giants: Kenya’s Foreign Policy Between the West and China in the 21st Century (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
In an era of shifting global power dynamics, the East African state of Kenya occupies a uniquely strategic position. Flanked by Indian Ocean access, regional trade routes, and a history of Western alliances, Kenya now finds itself recalibrating its foreign policy between traditional Western partners (especially the United States and European Union) and the rising influence of China. This paper argues that Kenya’s foreign policy in the 21st century reflects a deliberate Balancing Act: leveraging Chinese infrastructure investment and trade opportunities while trying to maintain the political, security, and normative benefits derived from its Western relationships. This balancing reflects both opportunity and risk: opportunity in terms of alternative sources of finance and strategic options, and risk in terms of dependency, sovereignty questions, and diplomatic pressure. Understanding this balance is critical not only for Kenya but also for broader debates on how middle‐power states navigate great-power competition in Africa.